Politische, kulturelle und wissenschaftliche Perspektiven der nachhaltigen Raumentwicklung in den Alpen - Borsdorf, Axel (alpine space - man and environment, 2006)
Conceived with the steering bodies of the Alpine Convention, DIAMONT aims to give a vital impulse to the relaunch of SOIA (System for Observation of and Information on the Alps). In consistence with SOIA's new aims and the European Spatial Development Perspective (ESDP), DIAMONT will take into account the expectations of experts for regional development as well as the needs of the Alpine population. The DIAMONT network of specialists on Alpine development will advise SOIA on the elaboration of an Alpine wide information system and the selection of relevant data considering their validity and their aptitude for harmonization. This process will involve a test of pilot tools for regional development and discussions with the population in test regions. DIAMONT integrates cultural, regional and local factors into the analysis and preparation of a sustainable regional development. The project's results will supply a method adaptable to other European mountain areas.